PASTORAL KONSELING MEMBANGUN KETANGGUHAN KELUARGA KRISTEN MELALUI PENDEKATAN HOLISTIK DI ERA MODERN - Lendo, Teydi; Londo, Frisca Elisabeth (PT. Giat Konseling Nusantara, 2025)
This article discusses the importance of pastoral counseling in building the resilience of Christian families in the modern era through a holistic approach. This study aims to determine how pastoral counseling can help Christian families in facing challenges in the modern era and building their resilience. The results of the study indicate that a holistic approach in pastoral counseling can help Christian families in increasing their harmony and resilience.